Long-term wear failure analysis of uhmwpe acetabular cup in total hip replacement - Shahemi, Nur Hidayah; Liza, Shahira; Abbas, Azlina Amir Mir; Merican, Azhar Mahmood (Elsevier, 2018)
A revision of a metal-on-ultra high molecular weight (UHMWPE) bearing couple for total hip replacement was performed due to aseptic loosening after 23 years in-vivo. It is a major long-term failure identified from wear generation. This study includes performing failure analysis of retrieved polyethylene acetabular cup from Zimmer Trilogy® Acetabular system. The UHMWPE acetabular cup was retrieved from a 61 years old male patient with ability to walk but limited leg movement when he presented to hospital in early 2016 with complaint left thigh pain. It was 23 years after his primary total hip replacement procedure. Surface roughness and morphology condition were measured using 3D laser microscope and Scanning Electron Microscope (SEM) to evaluate and characterize the wear features on polyethylene acetabular cup surface. ATR-Fourier Transform Infra-Red (ATR-FTIR), differential scanning calorimetry (DSC) and gel permeation chromatography (GPC) were used to characterize the chemical composition of carbon-oxygen bonding, crystallinity percentage and molecular weight of the polymer liner that might changes the mechanical properties of polyethylene. Nano indentation is to measure hardness and elasticity modulus where the ratio of hardness to elastic modulus value can be reflected as the degradation of mechanical properties. A prominent difference of thickness between two regions resulted from acentric loading concentration was observed and wear rate were measured. The linear wear rate for thin side and thick side were 0.33 mm/year and 0.05 mm/year respectively. Molecular weight reduction of 57.5% and relatively low ratio of hardness to elastic modulus (3.59 × 10−3) were the indicator of major mechanical properties degradation happened on UHMWPE acetabular cup. This major degradation was contributed by oxidation and polishing wear feature accompanied with delamination, craters, ripple and cracks were the indication of extensive usage of UHMWPE from the suggested life span of acetabular cup application.